Benign glandular schwannoma - Khaldoon Aljerian (University of São Paulo, 2022)
We report a case of a benign glandular schwannoma in a 63-year-old male who presented with a solitary subcutaneous mass on the left knee, with no previous history of neurofibromatosis type 1. This histological subtype is rare, with only 38 cases reported in the literature. Some of the glands found in this patient resembled sweat glands. These lining stromal spindle cells were positive for S-100 but negative for EMA. S100 was faintly staining the glandular elements. All the glands in the tumor were positive for EMA, particularly at the luminal borders. They were also positive for pancytokeratin. The cystic areas variably show intraluminal, foamy, and hemosiderin-laden macrophages. The different glands expressed two patterns. Some of these were reactive for CK7 and low molecular weight keratin. Immunohistochemical workup is mandatory to assess the neoplastic nature of this glandular component.